SPIROMICS Research Group. Clinical Significance of Symptoms in Smokers with Preserved Pulmonary Function - Torres-González, July (American journal of respiratory and critical care medicine, 2018)
N Engl J Med (14) Reviewed by July Torres-Gonzalez Two of the most important highlights of the new Global Initiative for Chronic Obstructive Lung Disease (GOLD) 2018 report are the possibility of spirometric instability and/or reversibility in COPD diagnosis (15, 16) and the recognition that "chronic respiratory symptoms may precede the development of airflow limitation and can be associated with acute respiratory events" (17); information from studies that describe important outcomes among symptomatic smokers with normal lung function could redefine COPD by including a new clinical entity, which has been referred to as COPD with normal spirometry (18, 19). All participants underwent spirometry, CAT score determination, 6MWT, and chest CT scans and were prospectively monitored for a median of 27 months to document exacerbations, defined on the basis of the use of systemic glucocorticoids and/or antibiotics, any health care utilization, or emergency department visits/hospitalization (severe exacerbations). Multivariable models controlling for important potential confounders (heart failure, gastroesophageal reflux, body mass index, and smoking) and sensitivity analysis excluding subjects with a history of asthma did not alter the results.